Comparison of efficacy of doxycycline and isotretinoin on cutaneous human beta-defensin-1 and -2 levels in acne vulgaris - Gulhan Aksoy; Esra Adisen; Ozlem Erdem; Ahmet Burhan Aksakal (Wolters Kluwer Medknow Publications, 2018)
Background: Recent studies have shown that human beta-defensin-1 (hBD-1) and (human beta-defensin-2 hBD-2), which are antimicrobial peptides produced by the skin, play a role in the pathogenesis of acne vulgaris (AV). Objective: The aim of this study was to determine the role of antimicrobial peptides in the pathogenesis of AV and enlighten the effects of doxycycline and isotretinoin in the expression of these defensins in AV. Materials and Methods: A total of 44 patients (22 patients in each group) with Grade 6 and 8 AV who were indicated doxycycline or isotretinoin for their treatment, and 20 healthy volunteers were included in this study. Pretreatment cutaneous samples were obtained from pustular lesions and uninvolved skin of AV patients and were repeated after the treatment. Only one biopsy was obtained from controls. Results: Cutaneous levels of hBD-1 and hBD-2 were significantly increased in AV patients when compared with healthy controls (P<0.05). Doxycycline therapy achieved a decrease in hBD-1 levels (P<0.05), whereas isotretinoin therapy achieved a reduction in hBD-2 levels when compared with pretreatment levels (P<0.05). Posttreatment hBD-1 and hBD-2 levels were not different between doxycycline and isotretinoin groups (P>0.05). Conclusion: In the light of these results, it was reasonable to assume the role of hBD-1 and hBD-2 in the pathogenesis of AV. Our results showing a significant reduction in hBD-1 staining with doxycycline treatment and in hBD-2 with isotretinoin suggested that some part of their anti-acne effect worked through these mechanisms.